Cendrars's Variegated Poetic Persona: Seduction and Authenticity in Prose of the Transsiberian and Nineteen Elastic Poems - Everett F. Jacobus Jr. (Studies in 20th & 21st Century Literature, 1979)
Since Cendrars recognizes the protean nature of his personal and public self, it is not surprising that the persona of his poetry escapes easy definition. My essay studies the consequences of this fact on the relationship between the poetic persona and his reader. Seduction, set against a Freudian and transactional-analysis conceptual background, provides a methodological metaphor for my analysis. In the same way that for Freud the real event of seduction only becomes psychologically effective as a fantasy and eventually as a structural pattern for the male-female relationship, our use of the seduction metaphor takes an initial naïve event between persona and reader and transforms it into a characteristic structural relationship. The persona's initial demand of intimacy from the reader is seen to be but one position in a narrative pattern which alternates the persona's attitude vis-a-vis his own narration between intimacy and detachment (or irony). The reader's role in connection with the persona is finally not one of sympathy but one of collaboration in inflecting a reading of the persona's narrated presence. Cendrars's manipulation of the persona-reader relationship is thus a primary component of his literary appeal.
Keywords: Blaise Cendrars; poetry; poetic persona; seduction; Freud